An Evaluation of the Quality of Commercial Nutrition Apps for Cancer Survivors. (14th June 2022) - Griffith, Hannah; Pozulp, Kendall; DiFilippo, Kristen; Lin, Annie
Abstract: Objectives: Mobile nutrition apps have the potential to address gaps within the cancer care continuum by providing nutrition education to shape one's knowledge. Few studies evaluate the quality of these cancer nutrition apps and the degree of clinician agreement on app quality. Thus, we investigated the quality of four cancer nutrition apps with knowledge shaping features. Methods: During December 2019, an initial search was conducted in the Apple App Store using keywords relevant to cancer and nutrition. Apps were chosen if they provided free cancer-specific nutrition education (i.e., knowledge shaping) regardless of accuracy (e.g., "anti-cancer" foods, recipes) and had a ≥3-star rating. Four apps with knowledge shaping features were evaluated: Eat AntiCancer, Get Well Soon, Untire, and Vegan Soul Belly. Five oncology dietitians used the validated App Quality Evaluation (AQEL) to rate apps in several domains, such as: knowledge shaping (knowledge acquisition, skill development) and app design (functionality, appropriateness for cancer survivorship). Domain scores ranged from 0 -10 (score ≥8 represented high quality). Interclass correlation coefficient (ICCs) analyses determined the interrater reliability between dietitians. An ICC ≥0.90 represented excellent agreement; 0.75 to < 0.90 as good; 0.50 to <0.75 as moderate; and <0.50 as poor. Fixed effects models were used to examine domain score differences between apps, adjusting for the rater. Statistical significance threshold was set at P <0.05. Results: All apps had good agreement with AQEL scores among the dietitians (ICC range = 0.75–0.82). When examining differences in AQEL scores among apps, Untire had the highest AQEL scores in the knowledge acquisition (mean: 8.0 ± 1.2; p = 0.02). There were no differences in skill development and app design between the cancer apps (p > 0.05). Only Untire scored highly in the knowledge acquisition, function, and appropriate for cancer survivorship domains (all AQEL ≥8). None of the apps received a high-quality score for skill development (AQEL <8). Conclusions: Untire received high-quality scores for knowledge acquisition and app design. None of the apps scored highly in skill development. Future cancer nutrition apps should consider including effective skill development features to assist with shaping knowledge for behavior change. Funding Sources: No funding sources.